Japan-South Korea trade dispute - Nguyen, Manh Linh; Sankot, Ondřej, 1988-; Kováčiková, Viera; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This study investigates the direct and indirect impacts of the Japan-South Korea trade conflict on the Korean semiconductor industry. Utilizing economic theories and the Global Value Chain framework, the research analyzes data from multiple sources, elucidating the intricate repercussions of the conflict. Despite limitations, the study emphasizes the importance of geopolitics in international trade and reveals the industry's resilience amidst disruptions. It paves the way for future research to delve into long-term strategies for conflict mitigation and potential expansion into other affected industries.
Vedoucí práce: Ondřej Sankot
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses